Digitalization of Technical Service Minutes as an Implementation of Paperless Office at PLN ULP Kisaran - Achmad Puariesthaufani N; Rachmat P.H Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
As a company engaged in the energy sector, PLN is aware of its contribution and important role in the issue of climate change and its application of sustainability in order to create harmony in economic growth and community social activities.This is all done in a way that ensures the fulfillment of the resources needed in the long term.The use of paper in routine operational activities in the PLN ULP unit reaches 28 reams per month and the use of paper in the engineering section is 33% or the second largest user of paper in the unit.The next fact is that only less than 50% of field officers who attach paper Minutes (BA) in disturbance service activities have an impact on the total use of paper material in units that contribute to emissions of 0.3 tons of CO2eq at the PLN ULP Kisaran. One such way is the implementation of Paperless Office. This concept is to minimize the use of paper in operational activities to reduce the impact of emissions directly or indirectly.On the other hand, company activities must be in line with other aspects such as corporate governance.Then a comprehensive understanding is needed in formulating policies that will be implemented. The paperless office implementation that we innovate is rooted in the inevitability of using technology in line with management demands to achieve the given challenges. The design of the digital Minutes aims to be aligned with fulfilling management's mission in the aspects of zero emissions, work effectiveness, accounting efficiency and good corporate governance.The result of this innovation is being able to reduce paper emissions by 0.18 per unit, as well as an efficiency of 11% -33% from the operational costs of using BA paper.